Analysing the Rise of Psychosexual Crimes in the Digital Age: A Legal Perspective - Kaushiki Parihar; Yagya Bharadawaj; Tanya Sinha (Journal of Psychosexual Health, 2026)
Objective: The article examines the escalation of technology-facilitated psychosexual crimes such as cyberstalking, online harassment, sextortion and child sexual abuse and highlights the role of digital technologies in facilitating anonymity and accessibility of such crimes, intensifying the mental suffering of the victims. The article examines the rise of psychosexual crimes in the digital age, evaluates the Indian legal framework’s effectiveness and identifies research gaps related to such crimes and enforcement challenges. Methods: The study is doctrinal in nature, primarily based on both qualitative and quantitative aspects. The study is based on government reports and statistics, case studies and a comparative legal framework between 2000 and 2025. The article evaluates technological facilitation, psychological motivations and legal responses by comparing the Indian legal framework with other countries. Results: Findings indicate anonymity in the existing legal provisions regarding the subject matter and the challenges associated with the lacuna in the legal system, which often lead to non-reporting or underreporting of psychosexual crimes. The advancement of the digital age has been driven by the expansion of the use of the internet and artificial intelligence and social media platforms have made interaction with humans quite convenient. However, they have also paved the way for numerous criminal activities, including psychosexual crimes, through which offenders of these crimes seek to gratify their psychosexual desires and needs. Conclusion: The study provides recommendations on how cyberspace can be regulated in a better manner to hold the perpetrators accountable and take appropriate legal action against them so that the victims get proper justice and these crimes can be curbed to make the digital space safer for the users. Thus, the study integrates psychological, technological and legal provisions to provide a technology-facilitated psychosexual crime.